2007
DOI: 10.1080/00365520600883777
|View full text |Cite
|
Sign up to set email alerts
|

Omeprazole reduces the response to capsaicin but not to methacholine in asthmatic patients with proximal reflux

Abstract: In asthmatics, inhibition of gastric acid secretion does not influence bronchial hyperresponsiveness but decreases tussive sensitivity and this effect is related to proximal reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
4
1
Order By: Relevance
“…In this regard, Ferrari and colleagues studied 17 patients with asthma and proximal reflux. They found that omeprazole reduced the cough sensitivity to capsaicin but did not alter airways reactivity to methacholine (28). Interestingly, previous studies have demonstrated that proximal acid reflux is predictive of a favorable response to acid suppressor therapy, although we did not find this in our trial (2,29).…”
Section: Discussioncontrasting
confidence: 76%
“…In this regard, Ferrari and colleagues studied 17 patients with asthma and proximal reflux. They found that omeprazole reduced the cough sensitivity to capsaicin but did not alter airways reactivity to methacholine (28). Interestingly, previous studies have demonstrated that proximal acid reflux is predictive of a favorable response to acid suppressor therapy, although we did not find this in our trial (2,29).…”
Section: Discussioncontrasting
confidence: 76%
“…Both have been recommended [Pratter et al 2006] and are widely used for a variety of airway reflux manifestations. There is some evidence of an effect, for instance a reduction in capsaicin cough sensitivity with omeprazole was demonstrated in patients with asthma [Ferrari et al 2007] but a recent randomised trial showed no effect of PPIs in poorly controlled asthma [Mastronarde et al 2009]. The authors concluded that reflux was not a significant contributor to poor asthma control, however the study proves only that acid reflux is not relevant.…”
Section: Pharmacological Agentsmentioning
confidence: 99%
“…Selectivity of TRPV1 regulation by acidic-induced inflammation is suggested by the observation that in asthmatics inhibition of gastric acid secretion does not influence bronchial hyperresponsiveness to methacholine, but decreases tussive sensitivity to capsaicin and this effect is related to proximal reflux (Ferrari et al 2007). The interaction between sensory nerve supply with the inflamed or injured tissue may follow nonobvious anatomical circuitry as acid instillation in the esophagus acutely increases the cough reflex sensitivity to capsaicin in patients with gastroesophageal reflux disease and chronic cough (Javorkova et al 2008).…”
Section: Discussionmentioning
confidence: 97%